Separate estimation of azimuth and elevation DOA using microphones located at apices of regular tetrahedron - Hioka, Y.; Hamada, N. (2004 IEEE International Conference on Acoustics, Speech and Signal Processing, 2004)
We propose a method for DOA (direction of arrival) estimation of speech signals in both azimuth and elevation directions. Our previous DOA estimation method achieves high precision and uniform spatial resolution by integrating the frequency array data (Hioka, Y. et al., J. Sig. Process., vol.7, no.1, p.105-9, 2003) generated from microphone pairs in an equilateral-triangular microphone array (Hioka and Hamada, N., IEICE Technical Report, EA2003-44, p.9-16, 2003). We now extend the method using four microphones located at the apices of a regular tetrahedron to enable the method to estimate the elevation angle from the array plane as well. Furthermore, we introduce an idea for separate estimation of azimuth and elevation to reduce the computational loads.